The Green House : New Directions in Sustainable Architecture and Design. - Stang, Alanna, ....-; Hawthorne, Christopher, ....- (New York : Princeton Architectural Press, 2010)
From the arid deserts of Tucson, Arizona to the icy forests of Poori, Finland to the tropical beaches of New South Wales, Australia to the urban jungle of downtown Manhattan, critics Alanna Stang and Christopher Hawthorne have traveled to the farthest reaches of the globe to find all that is new in the design of sustainable, or "green," homes. The result: more than thirty-five residences in fifteen countries -- and nearly every conceivable natural environment -- designed by a combination of star architects and heretofore unknown practitioners. Six different climactic zones are presented in The Green House -- waterfront, forest and mountain, tropical, desert, suburban, and urban; there is also a section on mobile dwellings. Each chapter features a series of homes that show the diversity and possibility of sustainable design. Projects are presented with large color images, plans, drawings, and an accompanying text that describes their green features and explains how they work with and in the environment. Architects included: Santiago Calatrava, Shigeru Ban, Miller/Hull, Rick Joy, Lake Flato, Kengo Kuma, Glenn Murcutt, Pugh & Scarpa, Werner Sobek, and many others. The Green House is not only a beautiful object in its own right, but is sure to be an indispensable reference for anyone building or interested in sustainable design -- and if you ask us, that should be everyone.
Keywords: Architectuur; Duurzaam bouwen; Ecologisch bouwen; Woningbouw